The neurobiological mechanism underlying hypothalamic GnRH pulse generation: the role of kisspeptin neurons in the arcuate nucleus - Plant, Tony M. (F1000Res, 2020)
This review recounts the origins and development of the concept of the hypothalamic gonadotropin-releasing hormone (GnRH) pulse generator. It starts in the late 1960s when striking rhythmic episodes of luteinizing hormone secretion, as reflected by circulating concentrations of this gonadotropin, were first observed in monkeys and ends in the present day. It is currently an exciting time witnessing the application, primarily to the mouse, of contemporary neurobiological approaches to delineate the mechanisms whereby Kiss1/NKB/Dyn (KNDy) neurons in the arcuate nucleus of the hypothalamus generate and time the pulsatile output of kisspeptin from their terminals in the median eminence that in turn dictates intermittent GnRH release and entry of this decapeptide into the primary plexus of the hypophysial portal circulation. The review concludes with an examination of questions that remain to be addressed.